2009
DOI: 10.1002/eji.200839037
|View full text |Cite
|
Sign up to set email alerts
|

CREB and AP‐1 activation regulates MKP‐1 induction by LPS or M‐CSF and their kinetics correlate with macrophage activation versus proliferation

Abstract: MAPK phosphatase-1 (MKP-1) is a protein phosphatase that plays a crucial role in innate immunity. This phosphatase inactivates ERK1/2, which are involved in two opposite functional activities of the macrophage, namely proliferation and activation. Here we found that although macrophage proliferation and activation induce MKP-1 with different kinetics, gene expression is mediated by the proximal promoter sequences localized between À380 and À180 bp. Mutagenesis experiments of the proximal element determined tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 79 publications
1
38
0
Order By: Relevance
“…Indeed, several AP-1 family or CREbinding proteins have been shown to translocate to the nucleus during LPS stimulation (Casals-Casas et al, 2009). According to our reporter gene assay, AP-1 appears to be blocked at a high concentration of Pa-EE (200 g/ml) (Fig.…”
Section: Fig 4 Effect Of Pa-ee On Etoh/hcl-induced Gastritis (A and B)mentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, several AP-1 family or CREbinding proteins have been shown to translocate to the nucleus during LPS stimulation (Casals-Casas et al, 2009). According to our reporter gene assay, AP-1 appears to be blocked at a high concentration of Pa-EE (200 g/ml) (Fig.…”
Section: Fig 4 Effect Of Pa-ee On Etoh/hcl-induced Gastritis (A and B)mentioning
confidence: 87%
“…It is well known that AP-1 and CREB are important transcription factors in LPS-mediated inflammatory responses (Proffitt et al, 1995;Casals-Casas et al, 2009). Indeed, several AP-1 family or CREbinding proteins have been shown to translocate to the nucleus during LPS stimulation (Casals-Casas et al, 2009).…”
Section: Fig 4 Effect Of Pa-ee On Etoh/hcl-induced Gastritis (A and B)mentioning
confidence: 99%
“…**p , 0.01, ***p , 0.001 in relation to the controls. Excessive macrophage activation has numerous damaging effects, exemplified in septic shock, which can lead to multiple organ dysfunction syndrome and death through a surplus of TNF-a production among other cytokines (33). In other situations, persistence of proinflammatory activity results in the development of chronic inflammation and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Two functional cAMP response element binding protein sites have been identified on the MKP1 promoter 64 and more recent studies have verified a role for cAMP response element binding protein and activator protein-1 as transcriptional activators of MKP1. 65,66 Another study ascribed GC-stimulated MKP1 expression to a tethering mechanism involving CCAAT/enhancer-binding protein ␤, independent of GC receptor-binding. 67 Conversely, a more recent study demonstrated a mechanism of MKP1 gene regulation by GCs involving GC receptor activity at a novel GC-responsive region.…”
Section: Discussionmentioning
confidence: 99%